Pengaruh Corporate Governance, Profitability, Dan Financial Distress Terhadap Tax Avoidance - Edgina, Mendy; Surjadi, Julisar (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The aim of this research was to obtain empirical evidence regarding the effect of the proportion of independent commissioners, audit committees, audit quality, profitability, firm size, institutional ownership, and financial distress on tax avoidance. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021. The research sample used a purposive sampling method with a total of 68 manufacturing companies listed on the Indonesia Stock Exchange used as samples in this study. Hypothesis testing and data analysis were carried out using a multiple linear regression model. The results of the study can be concluded that the variable audit committee and audit quality have an effect on tax avoidance, while the proportion of independent commissioners, profitability, firm size, institutional ownership, and financial distress have no effect on tax avoidance.